An Algorithm for Fingerprint Minutiae Extraction - Patel, Ronak B; Hiran, Dilendra; Patel, Jayesh M (International Journal of Computer Sciences and Engineering, 2019)
Human fingerprints are reliable characteristics for personnel identification as it is unique and persistence. Fingerprint biometric authentication is one of the challenging pattern Recognition problems. A Fingerprint pattern contains ridges, valleys and minutiae. Minutiae extraction is an important post-processing step of biometric fingerprint recognition system. The minutiae are key points and the main features of a fingerprint, with which you can compare one print with another. Generally minutiae extraction is carried out after different preprocessing stage like image enhancement and image thinning so image also contains large number of false minutia which can decrease the performance of the fingerprint recognition system. A novel algorithm of fingerprint minutia extraction is proposed in this paper: The algorithm work on the thinned binary image of the fingerprint, in order to eliminate the false minutiae.The implementation of research work is done in .Net platform using custom fingerprint database of 100 images of 25 users.